PENGARUH E-WOM TERHADAP BRAND IMAGE PERUSAHAAN (STUDI KASUS : MAYANG DAN TAN SKINCARE) - Dhita Putri Utami (PAWITRA KOMUNIKA : Jurnal Komunikasi dan Sosial Humaniora, 2024)
According to the We Are Social report as of 2022, world internet users will reach 4.95 billion, in Indonesia alone internet users have reached 204.7 million, in other words 73.7% of Indonesian people are internet users. It is recognized that the word of mouth strategy can play a large role in influencing consumers. In the past, word of mouth communication could only be done face to face, but along with technological developments, we can do word of mouth information via social media which has a wider reach and of course the impact on a company will be much stronger. This research aims to find out the influence of electronic word of mouth on the brand image of the case study companies Mayang and TAN Skincare. This research uses a qualitative approach with a primary data case study method in the form of quoted statements and data submitted by the Main Director of TAN Skin in various media in Indonesia. As reinforcement, this research also uses secondary data obtained from books, journals and previous research. The results of this research show that electronic word of mouth activities in the form of bad reviews about TAN Skin have negative impacts in terms of both material and non-material. TAN Skin stated that from the review submitted by Mayang Lucyana Fitri, the company suffered losses of up to hundreds of millions. Apart from that, TAN Skin also stated that it lost many consumers who had doubts about TAN Skin due to this case. This means that electronic word of mouth has a big influence on brand image and the increase or decrease in customers.